The future of human reproduction: Ectogenesis and transhumanism? - Álvarez Díaz, Jorge Alberto (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
This paper proposes that ectogenesis is a form of transhuman reproduction. Some of the advantages that have been found if ectogenesis is developed are mentioned, such as the liberation of women by freeing them from pregnancy, but they are accompanied by some criticism. From a case it is stated that there are problems that could arise from the development of ectogenesis that have not even been considered in the literature. Finally, it is proposed that perpetuating sexual dimorphism leads to perpetuating gender differences, so that the theoretical solution would be to eliminate sex in order to eliminate gender.